2006
DOI: 10.1089/ars.2006.8.1021
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative DNA Damage and Human Cancer: Need for Cohort Studies

Abstract: Research of the role of oxidative DNA damage is well established in experimental carcinogenesis. A large number of human studies on biomarkers of oxidative DNA damage, in particular related to guanine oxidation, have been published. The level of oxidative DNA damage and repair activity can be quite different between tumor and normal tissues; case-control studies have shown increased levels of oxidative DNA damage and decreased repair capacity in leukocytes from cases. Similarly, the urinary biomarkers of oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 92 publications
1
48
0
Order By: Relevance
“…[7] Thus, there has been growing interest in exercise-induced DNA damage due to its potential involvement in various diseases, since oxidatively damaged DNA has been implicated in carcinogenesis, ageing process, lifestylerelated diseases and age-related degenerative diseases. [40][41][42] Exercise-induced production of reactive oxygen and nitrogen species has been shown to cause oxidative stress to skeletal muscle, heart and other organs. As an adaptive response to exercise, antioxidant defense systems are upregulated, restoring intracellular prooxidant-antioxidant homeostasis.…”
Section: Wwwantioxorg Discussionmentioning
confidence: 99%
“…[7] Thus, there has been growing interest in exercise-induced DNA damage due to its potential involvement in various diseases, since oxidatively damaged DNA has been implicated in carcinogenesis, ageing process, lifestylerelated diseases and age-related degenerative diseases. [40][41][42] Exercise-induced production of reactive oxygen and nitrogen species has been shown to cause oxidative stress to skeletal muscle, heart and other organs. As an adaptive response to exercise, antioxidant defense systems are upregulated, restoring intracellular prooxidant-antioxidant homeostasis.…”
Section: Wwwantioxorg Discussionmentioning
confidence: 99%
“…However, changes in NOX expression or activation during conditions of acute or chronic lung disease are also suggestive of a potential contributing role for NOX in disease pathology. Indeed, it is well appreciated that chronic diseases of the respiratory tract, such as chronic obstructive pulmonary disease (COPD), asthma, cystic fibrosis, or various forms of lung cancer, are associated with increased oxidative stress and enhanced ROS production (194)(195)(196)(197), which may largely originate from enhanced and/or inappropriate NOX activation. To explain this paradox of beneficial and potentially detrimental effects of NOX enzymes, Lambeth recently proposed that NOX enzymes represent an example of antagonistic pleiotropy, meaning that potentially harmful genes are retained during evolution because they confer a reproductive advantage during early stages of life (198).…”
Section: Nox Enzymes In Lung Diseasementioning
confidence: 99%
“…Alternatively, DNA base oxidation products in cells, tissues, and urine can be measured by chromatographic methods. Urinary excretion products of oxidized DNA are considered as measurements of whole-body exposure representing repaired DNA lesions, sanitation of the nucleotide pool, and apoptosis (9). The chromatographically measurement of 8-oxodG in urine is considered to be more specific than the antibody-based ELISA method where insufficient specificity of the antibodies is a problem (10,11).…”
Section: Specificity Of Biomarkersmentioning
confidence: 99%
“…Oxidative stress is commonly regarded to be associated with various diseases such as cancer, coronary artery disease, and diabetes, but the biomarkers of oxidative stress may be elevated in patients as a consequence of the disease (28). The predictive value of biomarkers should be evaluated in prospective studies that may be a biobank-based type of cohort design (9). Using this type of approach, it has been shown that urinary excretion of 8-oxodG is a risk marker of lung cancer in non-smokers (29).…”
Section: Validation Status Of Biomarkersmentioning
confidence: 99%